Negotiation and the IPO Offer Price: A Comparison of Integer vs. Non-Integer IPOs - Bradley, Daniel J.; Cooney, John W.; Jordan, Bradford D.; Singh, Ajai K. (Journal of Financial and Quantitative Analysis, 2004)
Abstract We investigate the pricing of 4,989 equity IPOs with offer dates between 1981 and 2000. Approximately three-fourths of these IPOs have integer offer prices. Average initial returns for IPOs with integer offer prices are significantly higher (24.5%) than those priced on the fraction of the dollar (8.1%). This result is robust through time and after conditioning for other effects known to influence initial returns. We hypothesize that integer vs. fractional dollar IPOs are the result of negotiations between the issuing firm and underwriter. Under this negotiation hypothesis, the frequency of integer pricing should be an increasing function of the offer price and the degree of uncertainty surrounding the value of the firm. Empirical evidence, supportive of the negotiation hypothesis, is presented.